1999
DOI: 10.1161/01.cir.99.8.1041
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Among Electrophysiological Findings and Clinical Status, Heart Function, and Extent of DNA Mutation in Myotonic Dystrophy

Abstract: Prolongation of the HV interval is the most common conduction abnormality in MD and can be reliably recognized only by invasive EP testing. It raises the issue of prophylactic pacing to limit the incidence of sudden death in MD. Atrial and ventricular arrhythmias are often inducible, although their predictive value remains to be determined. Young age emerged as the most powerful predictor of inducible ventricular tachyarrhythmias. Conversely, we found no relationship between ECG or EP abnormalities recorded du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
86
0
6

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(96 citation statements)
references
References 34 publications
4
86
0
6
Order By: Relevance
“…Of note is the study by Lazarus et al (17); using precise invasive electrophysiological measurements, the study was unable to show such a relationship between conduction delays and the extent of CTG repeats. These differences among studies likely indicate that the conduction system is influenced by many other factors, some possibly still unidentified, that interact and create an unpredictable evolution of the conduction anomalies.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Of note is the study by Lazarus et al (17); using precise invasive electrophysiological measurements, the study was unable to show such a relationship between conduction delays and the extent of CTG repeats. These differences among studies likely indicate that the conduction system is influenced by many other factors, some possibly still unidentified, that interact and create an unpredictable evolution of the conduction anomalies.…”
Section: Discussionmentioning
confidence: 90%
“…Although such a correlation between the extent of CTG repeats and the degree of cardiac involvement has been described in some series, others have shown conflicting results (9,17,18,25,(34)(35)(36)(37)(38)(39). Of note is the study by Lazarus et al (17); using precise invasive electrophysiological measurements, the study was unable to show such a relationship between conduction delays and the extent of CTG repeats.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Regarding cardiac involvement, Tokgozoglu et al reported that myocardial wall motion and abnormalities in the electrocardiogram correlate with CTG-repeat length (20), whereas Lazarus et al reported that impediment of the atrioventricular conducting system does not correlate with CTG-repeat length (21). It remains uncertain whether this patient's cardiac involvement is severe or not; that is the patient has a potentially lethal arrhythmia, and the fatty infiltration was detected by biopsy of the cardiac muscle, but not detected by MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Plusieurs anomalies du système cardiovasculaire ont été observées (Phillips & Harper, 1997) et leur niveau de progression est généralement lent, mais demeure imprévisible (Antonini et al, 2000;Pelargonio, Dello Russo, Sanna, De Martino, & Bellocci, 2002 (Lazarus et al, 1999;Melacini et al, 1988).…”
Section: Complexité De La Prise En Chargeunclassified